A role for fibroblast growth factor receptor 1 in the pathogenesis of Neisseria meningitidis. (December 2020) - Azimi, Sheyda; Wheldon, Lee M.; Oldfield, Neil J.; Ala'Aldeen, Dlawer A.A.; Wooldridge, Karl G.
Abstract: Neisseria meningitidis (the meningococcus) remains an important cause of human disease, including meningitis and sepsis. Adaptation to the host environment includes many interactions with specific cell surface receptors, resulting in intracellular signalling and cytoskeletal rearrangements that contribute to pathogenesis. Here, we assessed the interactions between meningococci and Fibroblast Growth Factor Receptor 1-IIIc (FGFR1-IIIc): a receptor specific to endothelial cells of the microvasculature, including that of the blood-brain barrier. We show that the meningococcus recruits FGFR1-IIIc onto the surface of human blood microvascular endothelial cells (HBMECs). Furthermore, we demonstrate that expression of FGFR1-IIIc is required for optimal invasion of HBMECs by meningococci. We show that the ability of N. meningitidis to interact with the ligand-binding domain of FGFR1-IIIc is shared with the other pathogenic Neisseria species, N. gonorrhoeae, but not with commensal bacteria including non-pathogenic Neisseria species. Highlights: Fibroblast growth factor receptor (FGFR1) identified as an important receptor for meningococcal pathogenesis. FGFR1-IIIc interacts directly with meningococci but not other meningeal pathogens. FGFR1 is required for optimal invasion of human brain microvascular cells by meningococci.